New Integrals for Horn Hypergeometric Functions in Two Variables (Global Journal of Science Frontier Research, 2020)
In this paper, we establish several new integral representations of Euler-type involving Horn's functions G1,G2,G3,H1,H2,H5,H6 and H7. Some corollaries have also been obtained as special cases of our main results.
Keywords: gamma function; beta function; horn double functions; appell functions; eulerian integrals